Over-the-Counter versus Limit-Order Markets: The Role of Traders’ Expertise - Glode, Vincent; Opp, Christian C (Review of Financial Studies, 2020)
Abstract Over-the-counter (OTC) markets attract substantial trading volume despite exhibiting frictions absent in centralized limit-order markets. We compare the efficiency of OTC and limit-order markets when traders’ expertise is endogenous. We show that asymmetric access to counterparties in OTC markets yields increased rents from expertise acquisition for a few well-connected core traders. When the existence of gains to trade is uncertain, traders’ higher expertise in OTC markets can improve allocative efficiency. In contrast, when expertise primarily causes adverse selection, competitive limit-order markets tend to dominate. Our model provides guidance for policy makers and empiricists evaluating the efficiency of market structures.